Influence of Hotel Ambience and Performance of Hotels in Uganda. A Critical Literature Review - Kyule, Allan Kariuki (Journal of Modern Hospitality, 2022)
Purpose: Globally, there are over 160,000 star rated hotels with more than 14 million accommodation (rooms) available to millions of customers across low, middle and upmarket hotels. The overall objective of this study was to examine influence of hotel ambience and performance of hotels in upmarket areas. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concluded that upmarket hotel managers should improve and maintain consistency in service quality to enhance accommodation performance of their hotels. Upmarket hotel managers should place considerable importance on improving the levels of service reliability/trustworthiness, service reputation/credibility, and service recovery when something goes wrong, service accessibility/flexibility, service professionalism/skills and service behaviour/attitude in their daily operations. Upmarket hotel managers pay more attention to service quality delivery for better room efficiency and customer satisfaction. Unique Contribution to Theory, Policy and Practice: This study recommended that that the hotel regulatory authorities should improve on regulations and control of accommodation facilities to facilitate better accommodation performance of upmarket hotels. Upmarket hotel managers should consistently improve the quality of room facilities and service quality as well as support regulatory control to cause positive and significant changes in accommodation performance of upmarket hotels. The customers should use hotel star rating status as guide in comparing and making decisions on choice of accommodation facilities of upmarket hotels.